Alliances and evidence: Building the capacity and effectiveness of rural health advocacy in Australia. (10th October 2018) - Barclay, Lesley; Gregory, Gordon
Abstract: This article describes two strategies that have strengthened the capacity and effectiveness of rural health advocacy in Australia over the past nearly three decades. The first is the development of the National Rural Health Alliance, an organisation that grew from strategic efforts to develop relationships between rural and remote health practitioners and organisations. The second is the development, organisation and use of data and evidence to highlight rural health needs. There has been important synergy between these two streams of activity, with research and evidence providing the tools and the National Rural Health Alliance providing the strategy and techniques to influence the rural and remote health care agenda.